2012
DOI: 10.1177/0022034511435101
|View full text |Cite
|
Sign up to set email alerts
|

Increased Atherogenesis during Streptococcus mutans Infection in ApoE-null Mice

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. AbstrAct Streptococcus mutans, a dental caries pathogen, also causes endocarditis and is detected in atheroscelerotic plaque. We investigated the potential for an invasive strain of S. mutans, OMZ175, to accelerate plaque growth in apolipoprotein E deficient (ApoE null ) mice without and with balloon angioplasty (BA) injury, a model of restenosis. ApoE null mice were divided into 4 groups (N = 10), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 26 publications
2
56
0
Order By: Relevance
“…Briefly, proatherogenic ApoE null mice were used as a model for atherosclerosis [35], [36] and to examine the role of oral pathogen in induction of atherosclerosis [24], [25]. Male ApoE −/− B6.129P2- Apoe tm1Unc /J mice, eight-weeks-old (The Jackson Laboratories, Bar Harbor, ME) were kept in groups and housed in microisolator plastic cages.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, proatherogenic ApoE null mice were used as a model for atherosclerosis [35], [36] and to examine the role of oral pathogen in induction of atherosclerosis [24], [25]. Male ApoE −/− B6.129P2- Apoe tm1Unc /J mice, eight-weeks-old (The Jackson Laboratories, Bar Harbor, ME) were kept in groups and housed in microisolator plastic cages.…”
Section: Methodsmentioning
confidence: 99%
“…This ubiquitous infectious disease affects developed as well as non-developed countries with annual costs estimated by the American Dental Association to total over $40 billion annually in the United States alone. Additionally, S. mutans has been identified as a causative agent of infectious endocarditis (2)(3)(4)(5). Identifying how S. mutans interacts with host components at the molecular level is essential for a comprehensive understanding of the virulence properties of the organism.…”
mentioning
confidence: 99%
“…Previously, we showed that Cnm mediates the invasion of human coronary artery endothelial cells (HCAEC) in vitro and that Cnm ϩ strains exhibit increased virulence in the Galleria mellonella insect model (26). Moreover, recent investigation of S. mutans collagen-binding proteins (CBPs), such as Cnm and Cbm, has linked these adhesins with extraoral infections, including infective endocarditis, hemorrhagic stroke, and atherosclerotic plaque development (1,(27)(28)(29). To date, studies have focused on the role of Cnm in the extraoral virulence of S. mutans but have yet to elucidate whether Cnm confers any advantage on S. mutans in the colonization of oral tissues and the development of dental caries.…”
mentioning
confidence: 99%